THE CONCEPT OF NATIONAL PRIDE AND ITS REFLECTION IN FICTION LITERATURE - Sanobarkhan Karimova (Galaxy International Interdisciplinary Research Journal, 2022)
National pride as a spiritual feeling is formed in the material, political and moral development of society. As society develops, human needs also change, they differ from each other in terms of content and essence. National pride is also related to certain circumstances of the people, change of place of residence, renewal of the system in society. The concept of national pride is little studied, and different opinions are given about its nature and structure in philosophical literature. In the dictionaries of the Soviet period, the review is not visible, in some literature we can see that it was decided by the class point of view based on the demands of the politics of the time. In their view, national pride gives the concept of Soviet pride, the pride of the Soviet people.